1960
DOI: 10.1080/00288233.1960.10419308
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids and vitamin A in the blood of the bovine

Abstract: SummaryThis paper summarises results of carotenoid and vitamin A alcohol assays on a large number of individual blood samples taken from groups of pasture-fed dairy cows throughout the 1<954-55 to 1958-59 dairying seasons. Marked seasonal variations are shown to occur each year and attention is particularly drawn to the very large variability in the blood levels of carotenoids and vitamin A alcohol in individual animals of the 3ame breed.The effect, under pasture-feeding conditions, of factors such as breed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
2

Year Published

1962
1962
2002
2002

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
1
2
Order By: Relevance
“…Mean plasma CC values of 16.1 |ag ml 1 in spring and 12.5 |ag ml" 1 in autumn in heifers in this study were similar to concentrations found by McGillivray (1957McGillivray ( ,1960b for pasture-fed cows in spring and autumn. Higher plasma CC in J than F heifers was consistent with earlier reports of differences between these breeds (McGillivray 1960a;Morgan et al 1969).…”
Section: I-isupporting
confidence: 67%
See 2 more Smart Citations
“…Mean plasma CC values of 16.1 |ag ml 1 in spring and 12.5 |ag ml" 1 in autumn in heifers in this study were similar to concentrations found by McGillivray (1957McGillivray ( ,1960b for pasture-fed cows in spring and autumn. Higher plasma CC in J than F heifers was consistent with earlier reports of differences between these breeds (McGillivray 1960a;Morgan et al 1969).…”
Section: I-isupporting
confidence: 67%
“…These differences in plasma CC between breeds were reflected in the CC in milkfat; least squares means for concentrations in J (7.5 \ig g^1 fat) and F (5.2 |jg g" 1 fat) heifers were similar to those found in J and F heifers by Winkelman et al (1999) at similar stages of ssft Sft S lactation. Concentrations of CC in milkfat in this study were lower than those reported for samples of bulk milk taken from dairy factories in the Manawatu and Taranaki provinces over the October-December period (Keen & Wilson 1992) and for earlier reported concentrations (McGillivray 1957(McGillivray , 1960b). These differences may reflect cow-age effects, since heifers have lower plasma CC than mature cows (McGillivray 1960b).…”
Section: I-icontrasting
confidence: 50%
See 1 more Smart Citation
“…These steers may have had higher reserves of carotenoids in their fat depots when t h e trial commenced, a different rate of mobilisation of the carotenoids from the fat, or a greater ability to absorb more carotenoids from the diet. McGillivray (1960) and Morgan et al (1969) reported marked fat colour variations within, as well as between, breeds. Further work is required to detect such cattle to avoid extended periods of grain feeding just to improve their fat colour.…”
Section: Concentrations Of P-carotene and Lutein Significantlymentioning
confidence: 94%